(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
A series of Ni incorporated Mesostructured Silica Nanoparticles (MSN) were prepared by physical mixing method. Electrolyzed nickel oxide was used as the Ni precursor. The N2 adsorption-desorption and X-Ray diffraction (XRD) analyses evidenced that the increase in Ni loading decreased the surface area and crystallinity, and increased Ni particle size in the catalyst, respectively. The activity of CO2 reforming of CH4 followed the order of 10Ni/MSN > 15Ni/MSN > 5Ni/MSN > MSN. The highest activity was achieved by 10Ni/MSN with the CH4 and CO2 conversion of 63.4% and 87.2 %, respectively. The results indicated that the presence of a suitable Ni amount in MSN was beneficial to achieve high catalytic activity due to its effect on the amount of active metal sites available for the reaction. Thus, the electrolyzed nickel oxide precursor and Ni/MSN catalyst prepared by electrochemical method and physical mixing synthesis has a potential to be utilized in CO2 reforming of CH4.